DETERMINING CRITICAL SUCCESS FACTORS OF MOBILE BANKING ADOPTION IN IRAQ (World Bulletin of Management and Law, 2023)
The purpose behind using Mobile banking (M-banking) may bedescribed as one of the services offered by a bank or other financialorganization that enables its clients to do a range of banking activities using amobile device, like a tablet, personal digital assistant or smart phone .